Anticipating or accommodating to public concern? Risk amplification and the politics of precaution re-examined - Wardman, Jamie K.; Lofstedt, Ragnar (Wiley, 2018)
Regulatory use of the Precautionary Principle (PP) tends to be broadly characterized either as a responsible approach for safeguarding against health and environmental risks in the face of scientific uncertainties, or as ‘state mismanagement’ driven by undue political bias and public anxiety. However, the ‘anticipatory’ basis upon which governments variably draw a political warrant for adopting precautionary measures often remains ambiguous. Particularly, questions arise concerning whether the PP is employed pre-emptively by political elites from the ‘top-down’, or follows from more conventional democratic pressures exerted by citizens and other stakeholders from the ‘bottom-up’. This paper elucidates the role and impact of citizen involvement in the precautionary politics shaping policy discourse surrounding the UK Government’s ‘precautionary approach’ to mobile telecommunications technology and health. A case study is presented that critically re-examines the basis upon which UK Government action has been portrayed as an instance of anticipatory policymaking. Findings demonstrate that the use of the PP should not be interpreted in the preemptive terms communicated by UK Government officials alone, but also in relation to the wider social context of risk amplification and images of public concern formed adaptively in antagonistic precautionary discourse between citizens, politicians, industry, and the media, which surrounded cycles of Government policymaking. The paper discusses the sociocultural conditions and political dynamics underpinning public influence on government anticipation and responsiveness exemplified in this case, and concludes with research and policy implications for how society subsequently comes to terms with the emergence and precautionary governance of new technologies under conflict.